The Portrayal Of Discrimination Upon Native Americans In The Movie “Woman Walks Ahead (2017)” - Erika, Aisyah Rahma Putri (Syntax Corporation, 2025)
This study analyzes the representation of discrimination against Native American communities through the character of Sitting Bull in the film Woman Walks Ahead (2017). The film illustrates the cultural, political, and psychological pressures faced by the Lakota people due to U.S. colonial policies such as the Dawes Act and assimilation programs. Using a psychoanalytic approach based on Sigmund Freud’s theory, particularly the concepts of the id, ego, and superego, this research explores internal conflict, identity struggle, and psychological resilience within Sitting Bull’s resistance. The findings reveal that cinematic techniques such as lighting, framing, and sound are effectively employed to reinforce the portrayal of psychological oppression and silent resistance. This study highlights how film media serves as a platform for critiquing historical injustice and reinterpreting cultural identity.